Cloud Migration Analysis for Core System Infrastructure in Financial Services: Study Case PT XYZ - Hadinata, Stefanus Kevin; Aji , Rizal Fathoni (AI Society & STMIK Indonesia, 2024)
Currently, cloud computing adoption is being utilized in the financial sector for its flexibility and innovative technologies. This study assesses PT XYZ's readiness to migrate its core systems to a cloud environment, which is crucial for maintaining competitive agility and robustness in Indonesia's financial services sector. Focusing on the diffusion of innovations (DOI) model and the technology-organization-environment (TOE) framework, the research examines ten factors influencing PT XYZ's migration strategy. The analysis identifies challenges related to PT XYZ's aging on-premises infrastructure, including server procurement delays and maintenance issues, which impact operational efficiency. Through semi-structured interviews with key IT personnel, this study explores perceptions of the benefits and challenges of cloud computing, as well as regulatory compliance, aiming to guide PT XYZ toward a successful cloud migration that ensures continuity, compliance, and enhanced operational capabilities. The findings contribute to understanding the relative advantages, such as cost savings and security concerns, complexity, compatibility, technology readiness, top management support, firm size, competitive pressure, and regulatory factors. PT XYZ’s decision to migrate aligns with all the factors for cloud computing adoption, with the relative advantage, complexity, compatibility, technological readiness, and top management support being high impacts on the migration decision, while regulatory compliance presents a challenge for the financial services industry in Indonesia].